Nano-Chemotherapy synergize with immune checkpoint inhibitor- A better option? - Qian, Xinye; Hu, Wang; Yan, Jun (Frontiers in Immunology, 2022)
Immune checkpoint inhibitor (ICI) is one of the most important tumor treatment methods. Although the therapeutic efficiency of immune checkpoint inhibitor mono-therapy is limited, the combination of chemotherapy plus immune checkpoint inhibitors has shown great advantages in cancer treatment. This is mainly due to the fact that tumor reactive T cells could fully provide their anti-tumor function as chemotherapy could not only cause immunogenic cell death to increase antigen presentation, but also improve the immunosuppressive tumor micro-environment to synergize with immune checkpoint inhibitors. However, traditional chemotherapy still has shortcomings such as insufficient drug concentration in tumor region, short drug duration, drug resistance, major adverse events, etc, which might lead to the failure of the therapy. Nano chemotherapeutic drugs, which refer to chemotherapeutic drugs loaded in nano-based drug delivery system, could overcome the above shortcomings of traditional chemotherapeutic drugs to further improve the therapeutic effect of immune checkpoint inhibitors on tumors. Therefore, the scheme of nano chemotherapeutic drugs combined with immune checkpoint inhibitors might lead to improved outcome of cancer patients compared with the scheme of traditional chemotherapy combined with immune checkpoint inhibitors.